Analisis Strategi marketing Syariah Untuk Meningkatkan Minat Beli Konsumen Pada Kopi Kenangan Surabaya - Naqib, Ahmad An Naqib; Ajib Ridlwan, Ahmad (Universitas Negeri Surabaya, 2025)
The cafe industry is booming with the rise of local brands like Kopi Kenangan, which embraces the grab-and-go concept and leverages technology and social media to attract consumers. This study aims to avoid unfair competition and things that deviate from Shari'a because they generate business income that is not Halal, implementing a sharia marketing strategy (theistic, ethical, realistic, humanistic) can overcome this impact. Analyzing the sharia marketing strategy at Kopi Kenangan Surabaya is the goal chosen by the researchers. This research uses a descriptive qualitative research type, by obtaining data using observation, interviews, and documentation methods. This study uses primary and secondary data sources. The selected primary data sources are interviews with the Kopi Kenangan Surabaya Store Manager, employees, and consumers. Meanwhile, the secondary data sources are journals or literature on sharia marketing. Based on the research results, it can be concluded that the sharia marketing strategy to increase consumer buying interest in Kopi Kenangan Surabaya The Avenue MERR is considered to comply with Islamic law and has succeeded in increasing consumer buying interest with several supporting factors that influence consumer buying interest. It would be a good feeling if the research was carried out by looking for the influence of sharia marketing strategies that have an impact on consumer buying interest.